Evolución de la Capacidad Funcional y su Asociación con las Necesidades de Cuidado Paliativo en Adultos Mayores Institucionalizados - Duque López, Ana Clarybel; Rendón Hurtado, Karol Andrea (Universidad Antonio Nariño, 2023)
Introduction: This research proposal aims to identify the possible association between the need for palliative care with functional evolution in terms of frailty, changes in the level of independence, cognitive status and nutritional status, in institutionalized older adults in conditions of socioeconomic vulnerability